Lung Cancer Staging: Clinical and Radiologic Perspectives - Chheang, Sophie; Brown, Kathleen (Seminars in Interventional Radiology, 2013)
Published in 2009, the 7th edition of the American Joint Committee on Cancer TNM staging system is the culmination of an extensive worldwide initiative to standardize and validate lung cancer staging. Unlike prior editions, the new staging system is now inclusive of small cell carcinoma and carcinoid tumors. In addition, significant changes were made to the T and M descriptors, resulting in improved prognostic stratification of disease. This review article highlights these changes, the rationale for their inclusion in the new staging manual, and the role of the radiologist in determining stage.
Keywords: lung cancer; staging; TNM classification; imaging